AB0209 Optimisation of ultrasonographic examination for the diagnosis of erosive rheumatoid arthritis versus erosive osteoarthritis with radiography considered as gold standard. (12th June 2018) - Roux, C.; Gandjbakhch, F.; Pierreisnard, A.; Couderc, M.; Lukas, C.; Masri, R.; Sommier, J.-P.; Clerc-Urmes, I.; Baumann, C.; Chary-Valckenaere, I.; Loeuille, D.
Abstract : Background: Rheumatoid arthritis (RA) is the most prevalent chronic inflammatory joint disease 1, 2 responsible for structural damage. Radiography (RX) is considered as the gold standard for visualising and quantifying bone lesions in RA. 3 Musculoskeletal ultrasound (US) is booming in clinical practice for the diagnosis of RA. US can detect more erosions than RX at the joint level, especially at an early stage of the disease. 4 Objectives: To determine thresholds and better scenarios for the diagnosis of erosive RA by US in RA and osteoarthritic (OA) patients. Methods: Patients fulfilling ACR 1987 and/or ACR/ EULAR 2010 criteria for RA or hand OA criteria were prospectively included. A modified Sharp erosion score was assessed by two blinded readers and one adjudicator for discordant cases (number of eroded joints≤three). Erosions in US were scored on six bilateral joints (MCP2–3, 5; MTP2–3, 5) with a four-grade scale. Results: A total of 168 patients were included: 122 RA (32 early RA <2 years; 90 late RA ≥2 years); 46 OA patients. On RX: 42 RA patients (6 early; 36 late) and 5 OA patients were eroded according to ACR/ EULAR 2013 criteria (sensitivity: 34.4%, specificity: 89.1%). On US, 95 RA patients (21 early; 78 late) and 12 OA patients were eroded. Considering at least two joint facets eroded (threshold 1) or at least one joint facet eroded at grade 2 (threshold 2), sensitivities were good (68%–72.1%) and specificities excellent (89.1%–100%). With only six targeted joint facets examined, 73 and 74 patients were classified as erosive RA with threshold 1 and 2 with good sensitivities (59.8%–60.0%) and excellent specificities (95.6%–100%) respectively. For all scenarios, agreement between RX and US for the diagnosis of erosive RA was excellent (88.1% to 92.8%). Conclusions: US erosion assessment of six targeted joint facets permitted to detect 1.7 times more erosive RA patients than RX in late and early RA. References: [1] Guillemin F, et al. Prevalence of rheumatoid arthritis in France: 2001. Ann Rheum Dis. 2005Oct;64(10):1427–30. [2] Alamanos Y, et al. Incidence and prevalence of rheumatoid arthritis, based on the 1987 American College of Rheumatology criteria: a systematic review. Semin Arthritis Rheum. 2006Dec;36(3):182–8. [3] Baillet A, et al. Comparison of the efficacy of sonography, magnetic resonance imaging and conventional radiography for the detection of bone erosions in rheumatoid arthritis patients: a systematic review and meta-analysis. Rheumatol Oxf Engl. 2011 Jun;50(6):1137–47. [4] Wakefield RJ, et al. The value of sonography in the detection of bone erosions in patients with rheumatoid arthritis: a comparison with conventional radiography. Arthritis Rheum. 2000Dec;43(12):2762–70. Disclosure of Interest: None declared